Project-Based Learning-Science, Technology, Engineering, and Mathematics (PjBL-STEM): A Bibliometric Mapping of Themes and Research Gaps - Ali Usman; Selfi Maharani; Tri Asih Wahyu Hartati (International Journal of STEM Education for Sustainability, 2026)
This study aimed to examine the integration of Project-Based Learning (PjBL) in STEM education and identify research gaps. This study uses a bibliometric approach by analyzing 102 Scopus-indexed articles from 2014–2025. The analysis shows a significant increase in publications related to PjBL-STEM. Thematically, PjBL and STEM are interconnected core topics and form several research clusters, with the thinking skills cluster being the most central theme connected to issues of sustainable education and digital learning. Furthermore, keywords related to 21st-century competencies, such as critical and creative thinking, are more dominant than digital technologies, such as e-learning, artificial intelligence, machine learning, and learning analytics, which have not yet taken center stage in the research landscape. These findings indicate a gap in the integration of digital technologies in PjBL-STEM learning. Therefore, further research is recommended to focus on: (1) developing a digital technology-based PjBL-STEM model, (2) integrating learning analytics to monitor the learning process, and (3) strengthening data-based formative assessment to support 21st century skills.